Consumption and wealth in the long run: an integrated unobserved component approach - Malin Gardberg; Lorenzo Pozzi (Tinbergen Institute, 2018)
The ratio of consumption to total household wealth (i.e., tangible assets plus unobserved human wealth) is commonly calculated from the estimation of a log-linear version of the household intertemporal budget constraint as a cointegrating relationship between consumption, assets and earnings (i.e., the variable "cay"). The evidence in favor of a stable cointegrating relationship between these variables in the US is weak however. This paper follows an alternative empirical approach using an unobserved component model applied to US data over the period 1951Q4-2016Q4. The regression of consumption on assets and earnings is augmented with an unobserved stochastic trend, i.e., an integrated component. The results strongly support the presence of such an unobserved component in the consumption equation. We provide evidence that this component is related to financial liberalization which, by relaxing liquidity constraints of consumers, has permanently increased the consumption-to-wealth ratio over the sample period. We calculate an alternative "cay" variable, i.e., the stationary part of the consumption-to-wealth ratio, and find that its predictive ability for future (excess) stock returns is comparable to that of the standard "cay" variable.
Keywords: E21; C32; C11; 330; consumption; wealth; cay; financial liberalization; stationarity; excess returns; unobserved component; Bayesian